2014
DOI: 10.2466/21.02.pr0.115c14z7
|View full text |Cite
|
Sign up to set email alerts
|

Relations between Attachment, Resilience, and Earned Security in Japanese University Students

Abstract: This study investigated the relations between attachment, resilience, and earned security in Japanese university students. It was hypothesized that resilience would have a positive relationship with attachment and that people who had an insecure attachment style but high resilience would also have high earned security. An earned security scale was developed, based on the Naikan thought scale and attachment theory. The earned-security scales, a resilience scale, and an internal working model scale were administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 4 publications
1
13
1
Order By: Relevance
“…Such effect would be important to document also from a clinical perspective, as increased self-compassion may enhance compliance to challenging intervention (Rowe, Shepstone, Carnelley, Cavanagh, & Millings, 2016). Second, we assessed emotional resilience, as it is considered both a precondition and a product of stress perception, appraisal, and coping (Mikulincer & Shaver, 2007;Shibue & Kasai, 2014). In addition, it has previously been argued that earned attachment security later on in life, for instance through experiences with a supportive partner, may take their expression in heightened levels of self-reported resilience, while other features of the attachment working model may still be suggestive of insecure attachment (Shibue & Kasai, 2014).…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Such effect would be important to document also from a clinical perspective, as increased self-compassion may enhance compliance to challenging intervention (Rowe, Shepstone, Carnelley, Cavanagh, & Millings, 2016). Second, we assessed emotional resilience, as it is considered both a precondition and a product of stress perception, appraisal, and coping (Mikulincer & Shaver, 2007;Shibue & Kasai, 2014). In addition, it has previously been argued that earned attachment security later on in life, for instance through experiences with a supportive partner, may take their expression in heightened levels of self-reported resilience, while other features of the attachment working model may still be suggestive of insecure attachment (Shibue & Kasai, 2014).…”
Section: The Present Studymentioning
confidence: 99%
“…Second, we assessed emotional resilience, as it is considered both a precondition and a product of stress perception, appraisal, and coping (Mikulincer & Shaver, 2007;Shibue & Kasai, 2014). In addition, it has previously been argued that earned attachment security later on in life, for instance through experiences with a supportive partner, may take their expression in heightened levels of self-reported resilience, while other features of the attachment working model may still be suggestive of insecure attachment (Shibue & Kasai, 2014). This suggests that potential benefits from security priming may be reflected in increased emotional resilience even in the absence of changes in attachment security.…”
Section: The Present Studymentioning
confidence: 99%
“…In individuals faced with adverse life events, reduced resilience is associated with increased rates of depression, post-traumatic stress disorder (PTSD), and poor prognosis(23, 24). Other factors commonly associated with resilience include attachment style, spirituality, the tendency to experience positive emotions, and family and social support structures(25, 26).…”
Section: Introductionmentioning
confidence: 99%
“… 20 Similarly, the connection between attachment and resilience has been captured by several studies which found that students with higher anxious attachment had lower resilience. 13 , 21 In the current study we want to further expand this line of research by investigating the relationship between attachment, perceived stress, and resiliency in medical students.…”
Section: Introductionmentioning
confidence: 99%